Cost-effectiveness analysis of an intimate partner violence prevention intervention targeting men, women and couples in rural Ethiopia: Evidence from the Unite for a Better Life randomised controlled trial - Leight, Jessica; Deyessa, Negussie; Sharma, Vandana (BMJ, 2021)
Objectives: Experience of intimate partner violence (IPV) is associated with adverse health and psychosocial outcomes for women. However, rigorous economic evaluations of interventions targeting IPV prevention are rare. This paper analyses the cost-effectiveness of Unite for a Better Life (UBL), a gender-transformative intervention designed to prevent IPV and HIV risk behaviours among men, women and couples. Design: We use an economic evaluation nested within a large-scale cluster randomised controlled trial, analysing financial and economic costs tracked contemporaneously. Setting: UBL was implemented in rural southern Ethiopia between 2013 and 2015. Participants: The randomised controlled trial included 6770 households in 64 villages. Interventions: UBL is an intervention delivered within the context of the Ethiopian coffee ceremony, a culturally established forum for community discussion, and designed to assist participants to build skills for healthy, non-violent, equitable relationships. Primary and secondary outcome measures: This paper reports on the unit cost and cost-effectiveness of the interventions implemented. Cost-effectiveness is measured as the cost per case of past-year physical and/or sexual IPV averted. Results: The estimated annualised cost of developing and implementing UBL was 2015 US$296 772, or approximately 2015 US$74 per individual directly participating in the intervention and 2015 US$5 per person annually for each community-level beneficiary (woman of reproductive age in intervention communities). The estimated cost per case of past-year physical and/or sexual IPV averted was 2015 US$2726 for the sample of direct beneficiaries, and 2015 US$194 for the sample of all community-level beneficiaries. Conclusions: UBL is an effective and cost-effective intervention for the prevention of IPV in a low and middle-income country setting. Further research should explore strategies to quantify the positive effects of the intervention across other domains.